THE EFFECT OF SERVICE QUALITY AND PRICE ON CONSUMER SATISFACTION AT PT. AIR THE BEST LANGGA BRANCH KEPANJEN - Amara Puteri Wahyuning Ratih; Rizky Kurniawan Murtiyanto; Musthofa Hadi (Transpublika Publisher, 2024)
In today's modern era, business is one of the main pillars in the economy and social growth. To make the business more advanced and developed, consumer satisfaction is very necessary. In this context, to make consumers feel satisfied, companies need to pay attention to the products or services provided to fulfil what consumers expect. This was a quantitative research. The data collection was conducted by distributing questionnaires to 63 high school students who completed non- formal learning education at PT. Air The Best Langga Branch Kepanjen. This study utilised census sampling. The findings of the research revealed that service quality only has a limited impact on consumer satisfaction, whereas price has a significant impact on consumer satisfaction. According to the data, item X1.3 stands out with the lowest mean score of 39.4, indicating that the physical facilities at PT. Air The Best Langga Branch Kepanjen may not be up to par, leading to a lack of impact on consumer satisfaction by service quality. Nonetheless, both variables do have a substantial impact on consumer satisfaction, accounting for 73.5% of consumer satisfaction, while remaining 26.5% is influenced by other unaccounted factors. In conclusion, only price has a partial but significant effect on consumer satisfaction. PT. Air The Best Langga Branch Kepanjen should make a balance between price and service given to the consumers. If consumers feel the service quality is balance, or it can exceed consumer expectation, the company will create the consumer satisfaction toward PT. Air The Best Langga Branch Kepanjen.